Analisis Perencanaan Pajak Oleh Konsultan Pajak Dalam Meningkatkan Efektivitas Pengelolaan Pajak Klien (Studi Kasus Di Dwara Consulting) - Alfiany Hidayanti; Heriyanto Heriyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia's tax ratio in 2020 only reached 10.1%, while the Asia Pacific average was 19.1%. One of the causes of the low tax ratio is the practice of tax evasion and tax avoidance, as well as the lack of understanding of taxpayers in implementing effective tax planning. Tax consultants can help ease the tax burden without breaking the rules through a strategy known as tax planning. Companies need proper tax planning so that companies pay taxes efficiently without violating laws and regulations. The purpose of this study is to analyze tax planning by Dwara Consulting in improving the effectiveness of client tax management. Researchers used a qualitative research method with a case study research type. In this study, the theory used is the theory of tax planning by Barry Spitz. The results showed that the stages of tax planning carried out by Dwara Consulting include, analyzing the existing database, making one or more tax size plans, evaluating tax planning, finding weaknesses and improving the tax plan, and updating the tax plan. The tax planning carried out is in accordance with the stages of tax planning proposed by Barry Spitz in helping clients optimize tax obligations legally and efficiently..